The Effect of Mind Mapping on EFL Students’ Idea Development in Argumentative Writing across Gender Differences and Learning Styles - Ningrum, Ary Setya Budhi; Latief, Mohammad Adnan; Sulistyo, Gunadi Harry (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
The purpose of the study was to determine the impact of mind mapping as a strategy in generating ideas before writing on the EFL students’ idea development in argumentative writing as perceived from their gender differences and learning styles. By conducting an experimental investigation at university level in Indonesia, two existing TOEFL classes at the State Islamic Studies (STAIN) in Kediri were selected by a lottery to group 1: using linear notes (N=41), and group 2: using mind mapping (N=41). For analyzing the data, Analysis of covariance (ANCOVA) were utilized by using students’ TOEFL score as the covariate variable. The result findings indicated that there is no significant difference on the students’ idea developments in writing between the control and the experimental groups. These result also revealed that there is no significant difference on the students’ idea development in writing between gender differences, and among the students’ learning styles. Furthermore, there is no significant interaction between treatment and gender differences, and there is no significant interaction between treatment and learning styles.